Evaluating ChatGPT-4's Performance in Identifying Radiological Anatomy in FRCR Part 1 Examination Questions - Pradosh Kumar Sarangi; Suvrankar Datta; Braja Behari Panda; Swaha Panda; Himel Mondal (Indian Journal of Radiology and Imaging)
Background Radiology is critical for diagnosis and patient care, relying heavily on accurate image interpretation. Recent advancements in artificial intelligence (AI) and natural language processing (NLP) have raised interest in the potential of AI models to support radiologists, although robust research on AI performance in this field is still emerging.